2015
DOI: 10.1680/eacm.14.00023
|View full text |Cite
|
Sign up to set email alerts
|

Using corner chamfers to reduce the drag of flat-sided columns

Abstract: A comprehensive study of the drag forces acting on flat-sided columns is presented. The study considers a range of plane-sided column sections, from a sharp-cornered square section to varying degrees of corner chamfering and a full octagonal section. All chamfering was found to reduce the drag compared with the sharp-cornered case. It was also found there is a slight decrease in the drag coefficient as the Reynolds number of the fluid increases. For all cases except the octagonal section, drag increases signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The authors found that this structure reduced drag and discussed the fluid dynamical mechanism. Tong et al (2015) used chamfered corners to reduce the drag of 2D square cylinders with a sharp-angled square and octagonal cross section. The authors found that the chamfered structure reduces drag force compared with sharp corners.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that this structure reduced drag and discussed the fluid dynamical mechanism. Tong et al (2015) used chamfered corners to reduce the drag of 2D square cylinders with a sharp-angled square and octagonal cross section. The authors found that the chamfered structure reduces drag force compared with sharp corners.…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al [21] presented a numerical study for the flow over the chamfered square cylinders at varying degrees of chamfer and incident angles. It was concluded that chamfering reduced the drag coefficient compared with the sharp-cornered case.…”
Section: Introductionmentioning
confidence: 99%
“…After the wake flow measurements [6][7][8][9][10][11], Lyn and Rodi [12] conducted some experiments on the flapping shear layer formed by flow separation from the forward corner of a SC, with the associated recirculation region on the sidewall, and they found that the recirculation is an important aspect of some flow properties. For drag forces acting on flatsided columns, the study encompassed by Tong et al [13] revealed all chamfering can reduce the drag compared with the sharp-cornered case.…”
Section: Introductionmentioning
confidence: 99%